Resolution of Cochlear Inflammation: Novel Target for Preventing or Ameliorating Drug-, Noise- and Age-related Hearing Loss - Kalinec, Gilda M.; Lomberk, Gwen; Urrutia, Raul A.; Kalinec, Federico (Frontiers in Cellular Neuroscience, 2017)
A significant number of studies support the idea that inflammatory responses are intimately associated with drug-, noise-, and age-related hearing loss. Consequently, several clinical strategies aimed at reducing auditory dysfunction by preventing inflammation are currently under intense scrutiny. Inflammation, however, is a normal adaptive response aimed at restoring tissue functionality and homeostasis after infection, tissue injury and even stress under sterile conditions, and suppressing it could have unintended negative consequences. Therefore, an appropriate approach to prevent or ameliorate drug-, noise-, and age-related hearing loss should involve improving the resolution of the inflammatory process in the cochlea rather than inhibiting this phenomenon. The resolution of inflammation is not a passive response but rather an active, highly controlled and coordinated process. Inflammation by itself produces specialized pro-resolving mediators with critical functions, including essential fatty acid derivatives (lipoxins, resolvins, protectins and maresins), proteins and peptides such as annexin A1 and galectins, purines (adenosine), gaseous mediators (NO, H2S and CO), as well as neuromodulators like acetylcholine and netrin-1. In this review, we describe recent advances in the understanding of the resolution phase of inflammation and highlight therapeutic strategies that might be useful in preventing inflammation-induced cochlear damage. In particular, we emphasize beneficial approaches that have been tested in pre-clinical models of inflammatory responses induced by recognized ototoxic drugs such as cisplatin and aminoglycoside antibiotics. Since these studies suggest that improving the resolution process could be useful for the prevention of inflammation-associated diseases in humans, we discuss the potential application of similar strategies to prevent or mitigate drug-, noise-, and age-related hearing loss.